Comparison of organic substrates in urban rooftop agriculture, towards improving crop production resilience to temporary drought in Mediterranean cities. (17th April 2021) - Parada, Felipe; Ercilla‐Montserrat, Mireia; Arcas‐Pilz, Verónica; Lopez‐Capel, Elisa; Carazo, Núria; Montero, Juan I; Gabarrell, Xavier; Villalba, Gara; Rieradevall, Joan; Muñoz, Pere
Abstract: BACKGROUND: Urban agriculture contributes to meeting the growing food production demand in cities. In the context of low water availability, it is important to consider alternatives that are able to maintain production. Through a circular economy vision, this study aimed to assess the use of substrates made from local materials as an alternative for urban agriculture in periods of low water availability, due to water supply cuts. The substrates used were coir commercial organic substrate, vegetable compost from urban organic waste and perlite commercial standard substrate; a mixture of the urban compost and perlite (1:1) was used for three consecutive crop cycles of lettuce ( Lactuca sativa L. var. crispa ). The crop cycles were performed in the spring and summer periods of 2018 to observe the performance during warmer periods of the year in an integrated rooftop greenhouse near Barcelona. Each substrate was assessed under conventional irrigation (0–5 kPa) and temporary water restricted conditions (irrigation stopped until the water tension reached −20 kPa perlite). RESULTS: In terms of yield, our results show that the compost and mixture were similar to those obtained from perlite (11.5% and 3.7% more production under restricted water conditions). Organic substrates increased the crop's resilience to water restriction, in contrast to the perlite. In particular, water loss took longer in coir (one‐ and two‐crop cycle); however, when dryness began, it occurred quickly. CONCLUSION: The vegetable compost and the substrate mixture presented tolerance to temporary water restriction when water restriction reached −20 kPa. © 2021 Society of Chemical Industry.